Implementation of Civics Learning in Life Socializing With Students - Shafira Fortuna Hasibuan (International Journal of Students Education, 2024)
This research aims to determine the implementation of Civics learning in the social life of students. The method used in this research is the descriptive method. The data collection method used is observation, written tests, questionnaires and decommentation. The parameters used are student behavioral activities which include, reflect, the values of Civics learning that are obtained and implemented in the social life of students both in the classroom and outside the classroom, which has been implemented well, because learning is able to provide Civics values directly in the environment and the lives of the students themselves so that the students themselves can interact with each other in their daily lives. Based on the results, there are statement results that show the percentage of students who answered in the affirmative. So that parents and teachers work together to improve the ability of students to form social characters in their lives.